Political Power and State Institutions - Parezanović, Marko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Political power and state institutions, primarily in the sense of interweaving and reduction of their political power, is a research topic that has been going on for thousands of years. Many have studied the intertwined corridors of these political phenomena, but they have never been able to fully explore this topic. In this paper, their causal relationship is analyzed, with a special emphasis on the tendency of political power and state institutions to become alienated, in which these "servants of the people" are transferred over time to lords, which is why this paper starts from the position that political power wants to subordinate state institutions. The scientific importance is primarily contained in the effort to further enrich the scientific fund in the field of political theory and the state. The aim of the research is much more ambitious and is contained primarily in the intention to point out all the positive and negative repercussions that arise from the complex relations between the political power and state institutions, with the intention of pointing out these social anomalies and to increase the degree of democratization, but also functionality of society as a whole.